Potential Causal Association between Plasma Metabolites, Immunophenotypes, and Female Reproductive Disorders: A Two-Sample Mendelian Randomization Analysis - Hui-Hui Shen; Yang-Yang Zhang; Xuan-Yu Wang; Cheng-Jie Wang; Ying Wang; Jiang-Feng Ye; Ming-Qing Li (Biomolecules, 2024)
Background: While extensive research highlighted the involvement of metabolism and immune cells in female reproductive diseases, causality remains unestablished. Methods: Instrumental variables for 486 circulating metabolites (N = 7824) and 731 immunophenotypes (N = 3757) were derived from a genome-wide association study (GWAS) meta-analysis. FinnGen contributed data on 14 female reproductive disorders. A bidirectional two-sample Mendelian randomization study was performed to determine the relationships between exposures and outcomes. The robustness of results, potential heterogeneity, and horizontal pleiotropy were examined through sensitivity analysis. Results: High levels of mannose were found to be causally associated with increased risks of gestational diabetes (GDM) (OR [95% CI], 6.02 [2.85–12.73], p = 2.55 × 10−6). A genetically predicted elevation in the relative count of circulating CD28−CD25++CD8+ T cells was causally related to increased female infertility risk (OR [95% CI], 1.26 [1.14–1.40], p = 1.07 × 10−5), whereas a high absolute count of NKT cells reduced the risk of ectopic pregnancy (OR [95% CI], 0.87 [0.82–0.93], p = 5.94 × 10−6). These results remained consistent in sensitivity analyses. Conclusions: Our study supports mannose as a promising GDM biomarker and intervention target by integrating metabolomics and genomics.